Efficacy of befotertinib in non-small cell lung cancer harboring uncommon compound EGFR mutations G719X and S768I: a case report - Zhang, Zhedong; Huang, Yu; Gu, Haihua; Zhao, Lufeng; Zhao, Baiqin (Frontiers in Oncology, 2024)
The discovery of epidermal growth factor receptor (EGFR) somatic mutations and the availability of tyrosine kinase inhibitors (TKIs) as targeted therapies have transformed the treatment landscape for advanced non-small cell lung cancer (NSCLC). p.G719X and p.S768I mutations, often present in the form of complex mutations, are considered rare. This study firstly reported the treatment outcome of a locally advanced unresectable NSCLC patient with a rare complex EGFR p.G719X/ p.S768I mutations who received befotertinib. After treatment, the patient achieved partial response (PR), and no severe adverse events were observed. This case report supported befotertinib as a promising treatment option for advanced NSCLC patients with the rare p.G719X/ p.S768I complex mutations.